Investigating discrepancies in adsorption enthalpy predictions: An analysis of CO2 adsorption on HKUSTs - Liliana Giraldo; Juan Carlos Moreno-Piraján (Sustainable Chemistry for the Environment)
The pressing need to mitigate the presence of harmful gases in the atmosphere motivates scientific and engineering endeavors to devise effective adsorption solutions. Achieving practical and specific adsorption is essential for improving capture processes, with CO2 being a prominent target due to its significant environmental repercussions. Metal-organic frameworks (MOFs), distinguished by their high porosity and adaptable structure, have emerged as promising candidates for CO2 adsorption. Especially noteworthy are functionalized MOFs, which augment adsorption capacity, selectivity, and heat of adsorption. This research investigates CO2 adsorption on HKUST-1 modified with three amines of varying strengths, evaluating adsorption capacity and thermal impacts using direct adsorption calorimetry and Van't Hoff thermodynamic models.